(untitled) (History Journal «Jerónimo Zurita», 2025)
The essay aims to provide useful elements to clarify the early moments in the history of the monastery of San Leonardo in Chiusa Sclafani, whose reconstruction is made particularly complex by the homonymy between Nicola Count of Caltabellotta and his nephew Nicolò lord of Chiusa and by the loss of documents relating to the first foundation of the church of San Leonardo. Examination of the parchments of the Tabulario of Santa Maria del Bosco di Calatamauro and, in particular, of the concessions to the monastery made in 1421 by Nicolò and, in the 16th century, by his successors, has made it possible to define the role of the lord of Chiusa in the re-foundation and construction of the monastery. Born as a hospitium subject to the Benedictine monastery of San Martino delle Scale, it became, in 1529, infirmaria of the Olivetan abbey of Santa Maria del Bosco di Calatamauro, linking its history to the abbey until 1784.